Uma mãe, um mestiço, um epilético e uma prostituta: as irônicas interidentidades em O esplendor de Portugal (1997), de António Lobo Antunes - Cruz, Kairo Lazarini da (Universidade Federal de São Carlos, 2024)
This work aims to analyze the novel O Esplendor de Portugal (1997), by António Lobo Antunes, from a post-colonial perspective. Although this starting point is not exactly new, I hope that my reading proposal of the novel will enrich its critical reception with new points of view and highlight the importance of this approach in contemporary discussions about Portuguese identity. The dissertation is developed through two interconnected lines of analysis. Firstly, it’s based on Boaventura de Sousa Santos' (2003) concept of “interidentity”, which suggests that the self-representation of the Portuguese colonizer creates a disjunction between the subject and object of colonial representation. I examine the way in which the characters Isilda, Carlos, Rui and Clarisse, Portuguese settlers in Africa in the context of the historical end of colonialism and the subsequent Angolan Civil War (1975-2002), evoke geographic displacement and family breakdown as paradigmatic examples of this concept. Secondly, I argue that the notion of inter-identity allows to formulate an ironic subversion of symbolic systems that represent the colonial ethos of the Portuguese empire. From this point of view, the family microcosm of this novel can function as a model for a sustained critique of the notion of “Portugal's splendor” popularized by the official historiography of the Portuguese Estado Novo.

Este trabajo tiene como objetivo analizar la novela O Esplendor de Portugal (1997), de António Lobo Antunes, desde una perspectiva postcolonial. Aunque este punto de partida no es exactamente nuevo, espero que mi propuesta de lectura de la novela enriquezca su recepción crítica con nuevos puntos de vista y resalte la importancia de este enfoque en las discusiones contemporáneas sobre la identidad portuguesa. La disertación se desarrolla en dos líneas de análisis interconectadas. En primer lugar, recurro al concepto de “interidentidad” de Boaventura de Sousa Santos (2003), que sugiere que la auto-representación del colonizador portugués crea una disyunción entre el sujeto y el objeto de la representación colonial. Examino la forma en que los personajes Isilda, Carlos, Rui y Clarisse, colonos portugueses en África en el contexto del fin histórico del colonialismo y la subsiguiente Guerra Civil Angoleña (1975-2002), evocan el desplazamiento geográfico y la desintegración familiar como ejemplos paradigmáticos de este concepto. En segundo lugar, argumento que la noción de interidentidad permite articular una subversión irónica de los sistemas simbólicos que representan el ethos colonial del imperio portugués. Desde este punto de vista, el microcosmos familiar de esta novela puede funcionar como un modelo para una crítica sostenida de la noción del “esplendor de Portugal” popularizada por la historiografía oficial del Estado Novo portugués.
A mother, a mestizo, an epileptic, and a prostitute: the ironic interidentities in The Splendor of Portugal (1997), by António Lobo Antunes
Keywords: Interidentidade; Ironia; Colonialismo; Pós-colonialismo; Ficção portuguesa contemporânea; António Lobo Antunes; Interidentity; Irony; Colonialism; Postcolonialism; Contemporary portuguese fiction; Antonio Lobo Antunes; Interidentidad; Ironía; Colonialismo; Postcolonialismo; Ficción portuguesa contemporânea; António Lobo Antunes; LINGUISTICA, LETRAS E ARTES::LETRAS::LITERATURA COMPARADA; LINGUISTICA, LETRAS E ARTES::LETRAS::TEORIA LITERARIA